Dual Agency and Ethics Conflicts in Correctional Practice: Sources and Solutions - Cervantes, Ana Natasha; Hanson, Annette (Journal of the American Academy of Psychiatry and the Law Online, 2013)
Psychiatrists working in corrections, particularly in areas that have a shortage of forensic practitioners, may encounter a variety of ethics-related conflicts, especially when working both as clinicians and forensic evaluators within smaller systems. Such conflicts may include unavoidable dual treating and forensic evaluator relationships, and awareness of information that may complicate patient treatment or influence forensic opinions. Additional conflicts may arise if the psychiatrist is also retained privately to conduct forensic evaluations involving inmates in the same facility or facilities where the psychiatrist is otherwise employed, specifically because he may have duties to both a retaining party and an employer. Early-career psychiatrists, those who are completing their training in forensic psychiatry, and general psychiatrists who practice in corrections may be unfamiliar with the ethics-related dilemmas that arise in jails or prisons. Ethics courses during medical school and residency, while required, rarely discuss dilemmas specific to correctional settings. Furthermore, many psychiatrists practicing in corrections do not undergo formal training in forensic psychiatry, and even among different fellowship programs, the amount of time devoted to corrections varies significantly. The authors discuss hypothetical cases that reflect situations encountered, particularly by psychiatric fellows, forensic psychiatrists new to correctional work, and nonforensic clinicians working in corrections, a setting where dual agency is common and at times in conflict with core principles of ethics, including beneficence, nonmaleficence, neutrality, objectivity, and justice.